2009
DOI: 10.1177/0042098009346869
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Tenancy Sustainment Rates in British Social Rented Housing: The Roles of Management, Vulnerability and Choice

Abstract: Newman and Samoiloff, 2005). The policy concern reflects various perspectives. First, there are public service efficiency considerations, in the context where the management of social housing in the UK is becoming more deliberately focused on asset management strategies, in parallel with its European AbstractHigh rates of tenancy turnover in social rented housing have increasingly been identified as problematic both in the UK and elsewhere. High turnover has been variously associated with management failings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The affordability of mortgages, which is related to a number of economic factors including unemployment, low income and high mortgage payments (Whitley et al, 2004;Gerlach-Kristen & Lyons, 2018), was found to be the most important determinant. And the literature on tenancy sustainment finds that the most common reason for tenancy failure -the accrual of arrears -is a result of the precarious financial circumstances of tenants (Ambrose et al, 2015;Pawson and Munro, 2010).…”
Section: Understanding Rent Underpaymentmentioning
confidence: 99%
“…The affordability of mortgages, which is related to a number of economic factors including unemployment, low income and high mortgage payments (Whitley et al, 2004;Gerlach-Kristen & Lyons, 2018), was found to be the most important determinant. And the literature on tenancy sustainment finds that the most common reason for tenancy failure -the accrual of arrears -is a result of the precarious financial circumstances of tenants (Ambrose et al, 2015;Pawson and Munro, 2010).…”
Section: Understanding Rent Underpaymentmentioning
confidence: 99%
“…Whereas, quality of social rental in The Netherlands generally equates to that of owner-occupied stock, but older parts of the private rental sector are lower quality (Thomsen and van der Flier, 2007). However, strategy for improvement is large-scale demolition of older sub-standard social rental blocks and replacement with mixed tenure higher-quality dwellings, particularly in highland value areas (Norris and Coates (2010), Pawson and Munro (2010)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pawson and Munro have adeptly traced the unintended consequences of a high turnover in tenancy rates in social housing in both England and Scotland. Drawing on research by Gale, Cooper and Morris, they pinpoint key policy concerns associated with high turnover of tenancies.…”
Section: The New Flexible Tenancy Regimementioning
confidence: 99%
“…Several factors can be identified which render the private rented sector unfit for purpose in this homelessness context: The private sector offers few of the protections of long‐term security of tenure offered by local authority tenancies and historically has not developed with permanence and stability in mind, particularly not with a view to accommodating the vulnerable. Government statistics indicate that the loss of private sector tenancies is now the single greatest cause of homelessness in England. Under the reforms, it is anticipated that the homeless will find it more difficult than the general population to sustain their private sector tenancies thus further perpetuating individuals' homelessness status. Housing conditions in the private rented sector are often poor, with 33 per cent of the sector presently classed as ‘non‐decent’. Moreover, the quality monitoring systems in the private rented sector is far from rigorous.…”
Section: Changes To Homelessness Dutiesmentioning
confidence: 99%